1994
DOI: 10.2527/1994.7251325x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraruminal propionic acid infusion on metabolism of mesenteric- and portal-drained viscera in growing steers fed a forage diet: I. Volatile fatty acids, glucose, and lactate2

Abstract: This experiment investigated the effect of intraruminal infusion of propionic acid on ruminal VFA metabolism and the absorption of nutrients by the mesenteric- and portal-drained viscera of seven Friesian steers, average BW 127 kg, fed a dried grass-pellet diet. Each received by random allocation 0 (control), .5, or 1.0 mol of propionic acid/d for 7 d. Ruminal acetate and propionate irreversible loss rates and carbon exchange between VFA and CO2 were measured during continuous intraruminal infusions of 2-14C-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
68
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 27 publications
(32 reference statements)
13
68
2
Order By: Relevance
“…Both basal blood GTR and blood GTR during the glucose clamp procedure were enhanced by propionate supplementation. Seal and Parker [8] infused propionic acid into the rumen of growing steers at rates of 0.5 and 1.0 mol·day -1 , which were lower doses than in the present experiment when compared on a per BW basis, and reported that glucose irreversible loss rate increased at the higher propionic acid infusion rate (1.0 mol·day -1 ). On the contrary, Majdoub et al [7] reported that in growing lambs fed rye grass, the apparent glucose turnover was not modified by intraruminal infusion of propionate (0.55 and 0.91 mol·day -1 ), despite a numerical increase which was due to one of six animals.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Both basal blood GTR and blood GTR during the glucose clamp procedure were enhanced by propionate supplementation. Seal and Parker [8] infused propionic acid into the rumen of growing steers at rates of 0.5 and 1.0 mol·day -1 , which were lower doses than in the present experiment when compared on a per BW basis, and reported that glucose irreversible loss rate increased at the higher propionic acid infusion rate (1.0 mol·day -1 ). On the contrary, Majdoub et al [7] reported that in growing lambs fed rye grass, the apparent glucose turnover was not modified by intraruminal infusion of propionate (0.55 and 0.91 mol·day -1 ), despite a numerical increase which was due to one of six animals.…”
Section: Discussioncontrasting
confidence: 51%
“…Seal and Parker [8] found that in growing steers infused with propionate intraruminally, most of the infused propionate was converted to glucose. Van der Walt [2] reported that in sheep fed lucerne hay at 12-h intervals, 15 to 22% of glucose turnover derived from propionic acid even at the prefeeding period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majdoub et al [6] also reported modifications in lactate metabolism with propionate supplementation and suggested that these modifications were associated to modifications in glucose metabolism. Other authors [7,8] had reported an increase in glucose turnover in growing steers supplemented with propionate. An increased supply of propionate to growing lambs or to lactating cows has not however been systematically associated to a higher net hepatic production of glucose [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The effect on feed intake is the opposite of that expected if oxidation of glucose in enterocytes causes a satiety signal. (5) Intraruminal infusions of mixtures of acetate and propionate increase concentrations of these SCFA reaching the duodenum and unlike hepatocytes, enterocytes oxidise both acetate and propionate (91)(92)(93) . Therefore, oxidation of SCFA by enterocytes is an unlikely mechanism explaining differences in their hypophagic effects in ruminants.…”
Section: Weaknesses In the Modelmentioning
confidence: 99%